2D Phthalocyanine-Assembled Porous Nanostructure-Based Electrochemical Platform for High-Efficiency Detection of Ascorbic Acid - Jiang, Yuying (Langmuir : the ACS journal of surfaces and colloids, 2023)
In this work, a novel two-dimensional (2D) porous nanostructure is constructed upon air/water interfacial assembly of 12-crown-ether-4-incorporated double-decker phthalocyanine (Pc2). The combination of the good electroconductivity of phthalocyanine and the great surface area of the porous structure endows the assembled film with excellent chemical sensing property for ascorbic acid (AA). The low limit of detection can be 0.15 μM with a large linear concentration range and strong anti-interfering ability, which can be comparable to the best results of tetrapyrrole-based electrochemical sensors for AA. Furthermore, the obtained 2D porous assembled film sensor can be applied in real-time monitoring of AA in commercial drinks, indicating its application potential in accurate detection of AA in real samples